Tire cavity noise mitigation using acoustic absorbent materials - Zamri, Mohamed; Egab, Laith (Elsevier, 2020)
From past research, acoustic absorbent material is known to be effective in mitigating tire cavity noise. In this chapter, the use of felt material is studied by means of theoretical calculation, finite element simulation, and laboratory experiment to understand the science behind. The inclusion of felt material would increase acoustic damping from a given mathematical solution. The use of multilayer trim is shown as one of the options where electrical analogy was adopted to estimate the total increase in absorption coefficient which directly affects the reduction of tire cavity sound pressure level. The sound absorption coefficient of the trim was estimated using several empirical models found in the literature and compared with the normal incidence sound absorption coefficient measured by the impedance tube method.